Research on accurate and efficient coverage of 5G private network - Jingbo ZHAO; Shilei DONG; Tingyu HUANG; Mengxia CHEN; Peng HUANG (Dianxin kexue)
5G private network has become a new information infrastructure in all trades and professions because of its customizability, stable performance, safety and reliability.At the same time, due to the industry's higher requirements for business stability, certainty, energy conservation and low cost, 5G private network is urgently needed to achieve more accurate and efficient coverage than the public network.Taking the automated warehouse as a typical industry business scenario, a method to improve the accurate coverage of 5G private network by building a small experimental environment and optimizing the propagation model was proposed.Based on the refined modeling and simulation of the antenna gain of the typical space of the automated three-dimensional warehouse, combined with the test RSRP (Reference Signal Receiving Power) data of the typical space, the propagation model can be accurately corrected.According to the service level agreement (SLA) requirements of the industry terminal, the 5G private network accurate coverage parameters common to automated three-dimensional warehouses of different sizes can be obtained.